Perception Is Not Always and Everywhere Inferential. Issue 2 (3rd April 2018) - Hipólito, Inês
Abstract: This paper argues that it is possible to embrace the predictive processing framework (PP) without reducing affordances to inferential perception. The cognitivist account of PP contends that it can capture relational perception, such as affordances. The rationale for this claim is that over time, sensory data becomes highly-weighted. This paper, however, will show the inconsistency of this claim in the face of the cognitivist premise that 'encapsulated' models can throw away 'the body, the world, or other people' [Hohwy2016 : 265]. It is then showed how it is possible to embrace a non-cognitivist reading of PP—one that does not need to reduce affordances to representational content.